One pot synthesis of substituted 1H-benzo[f]chromen-3-yl-2H-chromen-2-one derivatives - Jagannadham, Yellanki; Ramadevi, Bhoomireddy; Prasanna, Bethanamudi (European Journal of Chemistry, 2017)
The title compounds, substituted 1H-benzo[f]chromen-3-yl-2H-chromen-2-ones were obtained by reacting 3-aryl-1-(3-coumarinyl)propen-1-ones with 2-napthol catalyzed by DBU (1,8-diazabicyclo[5,4,0]undec-7-ene) and concentrated H2SO4 in ample yields. Their structures were characterized by IR, 1H NMR, 13C NMR, mass spectral and elemental analysis. All the synthesized compounds have been evaluated for their in-vitro antibacterial activity against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa and antifungal activity against Aspergillus Niger and Candida albicans by using serial broth dilution method. Among those compounds 3 band 3c exhibits prominent results.